Forecasting government bond yields with large Bayesian VARs - Andrea Carriero; George Kapetanios; Massimiliano Marcellino (Queen Mary University of London, School of Economics and Finance, 2010)
We propose a new approach to forecasting the term structure of interest rates, which allows to efficiently extract the information contained in a large panel of yields. In particular, we use a large Bayesian Vector Autoregression (BVAR) with an optimal amount of shrinkage towards univariate AR models. Focusing on the U.S., we provide an extensive study on the forecasting performance of our proposed model relative to most of the existing alternative specifications. While most of the existing evidence focuses on statistical measures of forecast accuracy, we also evaluate the performance of the alternative forecasts when used within trading schemes or as a basis for portfolio allocation. We extensively check the robustness of our results via subsample analysis and via a data based Monte Carlo simulation. We find that: i) our proposed BVAR approach produces forecasts systematically more accurate than the random walk forecasts, though the gains are small; ii) some models beat the BVAR for a few selected maturities and forecast horizons, but they perform much worse than the BVAR in the remaining cases; iii) predictive gains with respect to the random walk have decreased over time; iv) different loss functions (i.e., statistical vs economic) lead to different ranking of specific models; v) modelling time variation in term premia is important and useful for forecasting.
Keywords: C11; C53; E43; E47; 330; Bayesian methods; forecasting; term structure; Prognoseverfahren; Bayes-Statistik; VAR-Modell; Zinsstruktur